FORMULATION OF MARKETING STRATEGY FOR PUPUK TRIKO SP PLUS (CASE STUDY OF SUNGEI PUTIH RESEARCH UNIT) IN GALANG DISTRICT, DELI SERDANG DISTRICT - Zulkifli, Tina (AGRIBUSINESS JOURNAL, 2024)
This research was conducted with the aim of identifying internal and external environmental factors, formulating alternative strategies, and establishing the main priorities of the Triko SP Plus fertilizer marketing strategy. The analytical method used is SWOT analysis and QSPM. The results of this study are the SO strategy of utilizing strategic production locations and the development of digital technology to expand the scope of marketing of fertilizers at affordable prices and products that have proven effective. The WO strategy utilizes the development of digital technology to cooperate with the government at every related event so that it can promote fertilizer in order to gain a wider range of market access. ST's strategy is to increase capital investment in the context of product development by utilizing research experts so that products are not easily competed with competitors from outside the region or competitors with better quality. And the WT Strategy informs about product superiority and establishes cooperative relationships in order to minimize the threat of competitors from outside the region and competitors with better product quality so that companies produce more products due to consumer demand that remains even increasing.